El proyecto urbano inclusivo como instrumento de la gestión territorial - Salvarredy, Julián Raúl (2021)
In the process of territorializing inequality, which results in the systematic exclusion of a large percentage of the population from the rights to housing and the city, between 10 and 70% of urban people in Latin America self-build their neighborhoods through social production of habitat. Public improvement policies (PMB), aimed in most cases at socially produced territories, have become the most advanced and widespread type of inclusive intervention in Latin America. \nThis thesis is historically based on the state of the issue both in relation to urban studies and with regard to the implementation of public policies for improvement. In this research process, which encompasses the theoretical framework and the background of practical implementation, it is possible to organize the variables that structure the work. The simultaneous implementation of various improvement programmes on socially produced urban sectors has led to the emergence of a new way of implementing territorial management, called the "inclusive urban project". In order to identify traits that have favored the scope of inclusive objectives and establish guidelines that guide future implementations of such public improvement policies, a comparative case study is developed to analyze them from such a perspective. \nIn the Metropolitan Area of Buenos Aires, a multiplicity of programs were developed in recent decades, which in many cases were applied simultaneously in the same sectors. This makes it an appropriate territory to place this research, together with the possibility of accessing the information necessary to study these processes in depth, to realize from these tutorials the conceptual and operational redefinition intended. \nIn this case, after conducting this systematic study, the inclusive urban project is developed conceptually and operationally as an instrument of territorial management, a guide to the intervention of public policies for improvement. Finally, its inclusive effects will be found in cases to support the recent application of its structural aspects.